Nanotherapy therapy for acute respiratory distress syndrome: a review - Yu, Yilai; Qiu, Liping (Frontiers in Medicine, 2024)
Acute Respiratory Distress Syndrome (ARDS) is a complex and life-threatening disease characterized by severe respiratory failure. The lethality of ARDS remains alarmingly high, especially with the persistent ravages of coronavirus disease 2019 (COVID-19) in recent years.ARDS is one of the major complications of neocoronavirus pneumonia and the leading cause of death in infected patients. The large-scale outbreak of COVID-19 has greatly increased the incidence and mortality of ARDS. Despite advancements in our understanding of the causes and mechanisms of ARDS, the current clinical practice is still limited to the use of supportive medications to alleviate its progression. However, there remains a pressing need for effective therapeutic drugs to combat this devastating disease. In this comprehensive review, we discuss the commonly used therapeutic drugs for ARDS, including steroids, vitamin C, targeted inhibitors, and heparin. While these medications have shown some promise in managing ARDS, there is still a significant gap in the availability of definitive treatments. Moreover, we highlight the potential of nanocarrier delivery systems, such as liposomes, lipid nanoparticles, polymer nanoparticles, and inorganic nanoparticles, as promising therapeutic approaches for ARDS in the future. These innovative delivery systems have demonstrated encouraging results in early clinical trials and offer the potential for more targeted and effective treatment options. Despite the promising early results, further clinical trials are necessary to fully assess the efficacy and safety of nanotherapiesfor ARDS. Additionally, more in-depth research should be conducted to focus on the continuous development of precision therapies targeting different stages of ARDS development or different triggers. This will provide more ideas and rationale for the treatment of ARDS and ultimately lead to better patient outcomes.